Constructing Dynamic Anode/Electrolyte Interfaces Coupled with Regulated Solvation Structures for Long‐Term and Highly Reversible Zinc Metal Anodes - Han, Mei‐Chen; Zhang, Jia‐Hao; Yu, Chun‐Yu; Yu, Jia‐Cheng; Wang, Yong‐Xin; Jiang, Zhi‐Guo; Yao, Ming; Xie, Gang; Yu, Zhong‐Zhen; Qu, Jin (Angewandte Chemie International Edition, 2024)
Aqueous zinc ion batteries (AZIBs) show a great potential for next‐generation energy storage due to their high safety and high energy density. However, the severe side reactions of zinc negative electrode largely hinder the further application of AZIBs. Herein, trace tris(hydroxymethyl)aminomethane (Tris) additive with rich lone‐pair‐electrons and zincophilic sites is firstly introduced to achieve long‐term and highly reversible Zn plating/stripping. Specifically, Tris not only regulates the solvation structure of Zn2+, but is also adsorbed vertically on the Zn anode surface with a changed coordination intensity during the plating/stripping process of Zn to generate an in situ dynamic adsorption layer for the first time. The dynamic adsorption layer could successively attract the solvated Zn2+ and then promote the de‐solvation of the solvated Zn2+ owing to the orientation polarization with regularly‐changed applied electric field, the volume rejection effect, and strong intermolecular force towards H2O of the vertically‐adsorbed Tris. Therefore, an improved Zn2+‐transport kinetics as well as the inhibition of side reactions of Zn anode are successfully realized. Accordingly, the Zn||Zn symmetric cell provides an ultra‐long cycle life of 2600 h. Furthermore, the Zn||MnO2 full cell with Tris could demonstrate a high capacity and structural stability for practical applications. A dynamic anode/electrolyte interface coupled with regulated solvation structures strategy is firstly realized with Tris additive for aqueous zinc‐ion batteries. The dynamic adsorption layer could successively attract solvated‐Zn2+, then promote the de‐solvation by the orientation polarization, the volume rejection effect and strong intermolecular force of the vertically‐adsorbed Tris, leading to an improved Zn2+‐transport kinetics and the inhibition of side reactions.